Urban Planning and Landscape Projects on Urban Riverbanks in Europe: Comparative Study of the Ebro River, Zaragoza, and the Isar River, Munich - María Pilar Sopena Porta; Francisco Pellicer (Urban Science)
The tension between rivers and cities reaches its highest expression in urban river basins. Given the high level of interaction between natural and cultural factors in many riverfronts, an integral project design is essential. The large number of urban river basin enhancement cases that have been conducted has resulted in a large amount of urban scientific literature. The multifaceted nature of these systems renders their analysis and contextualization a challenging endeavor. The objective of this research is to propose a novel evaluation tool based on a reformulation of Lynch’s theory of urban form performance, which has been updated from a landscape urbanism perspective. The conceptual framework provides a comprehensive method for translating diverse design strategies into comparable and meaningful categories. The results illustrate the impact of urban riverbank requalification initiatives on the formal quality dimensions of the city–river socio-ecological system. The assessment tool was applied to two cases: the Ebro River in Zaragoza (Spain) and the Isar River in Munich (Germany). Despite differences between the cases, comparative analysis revealed similar levels of urban landscape quality parameters and common elements that can provide new insights when considering the solutions applied and the degree of improvement in quality and river–city cohesion achieved with these projects.